Tannic Acid as a Natural Crosslinker for Catalyst-Free Silicone Elastomers From Hydrogen Bonding to Covalent Bonding - Kong, Sen; Wang, Rui; Feng, Shengyu; Wang, Dengxu (Frontiers in Chemistry, 2021)
The construction of silicone elastomers crosslinked by a natural crosslinker under a catalyst-free method is highly desirable. Herein we present catalyst-free silicone elastomers (SEs) by simply introducing tannic acid (TA) as a natural crosslinker when using poly(aminopropylmethylsiloxane-co-dimethylsiloxane) (PAPMS) as the base polymer. The crosslinked bonding of these SEs can be easily changed from hydrogen bonding to covalent bonding by altering the curing reaction from room temperature to heating condition. The formability and mechanical properties of the SEs can be tuned by altering various factors, including processing technique, the amount of TA and aminopropyl-terminated polydimethylsiloxane, the molecular weight and -NH2 content of PAPMS, and the amount of reinforcing filler. The hydrogen bonding was proved by the reversible crosslinking of the elastomers, which can be gradually dissolved in tetrahydrofuran and re-formed after removing the solvent. The covalent bonding was proved by a model reaction of catechol and n-decylamine and occurred through a combination of hydroxylamine reaction and Michael addition reaction. These elastomers exhibit good thermal stability and excellent hydrophobic property and can bond iron sheets to hold the weight of 500 g, indicating their promising applications as adhesives. These results reveal that TA as a natural product is a suitable “green” crosslinker for the construction of catalyst-free silicone elastomers by a simple crosslinking strategy. Under this strategy, TA and more natural polyphenols could be certainly utilized as crosslinkers to fabricate more organic elastomers by selecting amine-containing polymers and further explore their extensive applications in adhesives, sealants, insulators, sensors, and so forth.